Interventions to reduce bullying in health care organizations: A scoping review. (February 2014) - Quinlan, Elizabeth; Robertson, Susan; Miller, Natasha; Robertson-Boersma, Danielle
The problem of staff-to-staff bullying and its consequences in the health care sector has given rise to urgent knowledge needs among health care employers, union representatives, and professional associations. The purpose of this scoping review is to increase the uptake and application of synthesized research results of interventions designed to address bullying among coworkers within health care workplaces. The scoping review's methodology uses an adapted version of the Arksey and O'Malley framework to locate and review empirical studies involving interventions designed to address bullying in health care workplaces. The findings of the review reveal eight articles from three countries discussing interventions that included educative programming, bullying champions/advocates, and zero-tolerance policies. The reported evaluations extend beyond bullying to include organizational culture, trust in management, retention rates, and psychosocial health. The most promising reported outcomes are from participatory interventions. The results of the review make a compelling case for bullying interventions based on participatory principles.